Planning Problems in the Improvement of Access to Emergency Obstetric Care in Eastern Indonesia - Frederika Rambu Ngana; AAIN Eka Karyawati (GLOBAL HEALTH SCIENCE GROUP, 2021)
Maternal death is the worst performing of the Millennium Development Goals (MDGs) and Indonesia did not achieve its MDG #5 target in 2015. Therefore, the Indonesian government needs to review its strategies to decrease maternal deaths. One cause of maternal death is a lack of infrastructure, which can delay reaching emergency obstetric care (called Poned). This qualitative study investigated problems with priority planning in the Kupang district in order to improve access to emergency obstetric care (EMOC). A number of observations were conducted in the musrenbang (the district planning process). Interviews were carried out to gain an insight into the planning process from village to district level. A model for travel time to EMOC was created to support this study. In this study, six problems were identified in the district planning (musrenbang) regarding improving access to EMOCs. Those were (1) no planning proposal about improving access to EMOC, (2) budget constraints, (3) decision on the priority planning not being based on the level of urgency, (4) undue political influence, (5) lack of evidence and (6) incorrect measure of accessibility to obstetric care. Hence, to improve access to EMOC, scenario modelling with combined cost-benefit analyses (CBA) as an evidence-based planning should be applied in the musrenbang. It will help the health planners in Eastern Indonesia to gain a deep understanding about the problems in district planning process for access improvement to EMOC. Scenario modelling with CBA could provide the evidence during musrenbang.